2021
DOI: 10.3389/fendo.2021.687244
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ki67 in Evaluating Neoadjuvant Endocrine Therapy of Hormone Receptor-Positive Breast Cancer

Abstract: Ki67 is a proliferation marker. It has been proposed as a useful clinical marker for breast cancer subtype classification, prognosis, and prediction of therapeutic response. But the questionable analytical validity of Ki67 prevents its widespread adoption of these measures for treatment decisions in breast cancer. Currently, Ki67 has been tested as a predictive marker for chemotherapy using clinical and pathological response as endpoints in neoadjuvant endocrine therapy. Ki67 can be used as a predictor to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 64 publications
0
47
0
2
Order By: Relevance
“…Ki67 is a nuclear protein that marks active cell proliferation, both in normal and tumoral cells [ 30 ]. Specifically, this protein is used as a marker for the classification, prognosis, and prediction of therapeutic response in breast cancer [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ki67 is a nuclear protein that marks active cell proliferation, both in normal and tumoral cells [ 30 ]. Specifically, this protein is used as a marker for the classification, prognosis, and prediction of therapeutic response in breast cancer [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ki67 is a nuclear protein that marks active cell proliferation, both in normal and tumoral cells [ 30 ]. Specifically, this protein is used as a marker for the classification, prognosis, and prediction of therapeutic response in breast cancer [ 30 ]. This protein is expressed in all active phases of the cell cycle and decreases its expression after mitosis, in G0 phase [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…A series of studies demonstrated that Ki67 was highly correlated with poor prognosis in prostate, lung, serous ovarian and pancreatic cancers (21)(22)(23)(24)(25)(26). In breast cancer especially, Ki67 can be used as a determination index for luminal classification and is considered a "therapeutic window" for adjuvant or neoadjuvant therapy (27)(28)(29)(30)(31). A Series of studies on melanoma found a correlation between Ki67 expression and patient prognosis, with increased Ki67 expression being associated with an unfavorable prognosis (17,19,32,33).…”
Section: Discussionmentioning
confidence: 99%
“…This descriptive analysis found that most cases had hormonal and HER2 markers and a very low percentage had the Ki-67 marker, showing that molecular classification data was incomplete. The descriptive analysis also found that ensuring complete molecular classification requires labelling the molecular marker set mandatory data [18][19][20][21][22][23].…”
Section: Quality Of Breast Cancer Data Obtainedmentioning
confidence: 99%